2007
DOI: 10.1016/j.earlhumdev.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of maternal smoking to psychological problems in the offspring

Abstract: There is strong evidence for an association between maternal smoking in pregnancy and psychological problems in offspring. The problems most frequently associated are attention problems, hyperactivity, and conduct problems, although there is some evidence for an association with substance use problems as well. The nature of this association is unclear, but it is likely the result of a number of different mechanisms. Animal studies provide evidence for a causal relationship, in which exposure to nicotine has de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 28 publications
3
68
1
1
Order By: Relevance
“…Our findings replicate the positive relationship between prenatal tobacco exposure and diverse negative mental health outcomes in childhood (Ashford et al, 2008;Brennan et al, 2002;Button et al, 2007;Cornelius & Day, 2009;Ekblad et al, 2010;Ernst et al, 2001;Linnet et al, 2003;Nomura et al, 2010;Rogers, 2009), including externalizing problems of attention deficit hyperactivity and conduct problems and internalizing problems of emotional and peer (isolation) problems; in contrast, prenatal tobacco exposure was inversely associated with a positive mental health outcome of prosocial behaviors. More importantly, we demonstrated that heightened stress reactivity mediated the prospective influence of prenatal tobacco exposure on both externalizing and internalizing problems, even after controlling for an array of potential confounders.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our findings replicate the positive relationship between prenatal tobacco exposure and diverse negative mental health outcomes in childhood (Ashford et al, 2008;Brennan et al, 2002;Button et al, 2007;Cornelius & Day, 2009;Ekblad et al, 2010;Ernst et al, 2001;Linnet et al, 2003;Nomura et al, 2010;Rogers, 2009), including externalizing problems of attention deficit hyperactivity and conduct problems and internalizing problems of emotional and peer (isolation) problems; in contrast, prenatal tobacco exposure was inversely associated with a positive mental health outcome of prosocial behaviors. More importantly, we demonstrated that heightened stress reactivity mediated the prospective influence of prenatal tobacco exposure on both externalizing and internalizing problems, even after controlling for an array of potential confounders.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to these physiological effects, children exposed to tobacco smoke in utero also have an increased risk of psychiatric morbidity (Ekblad, Gissler, Lehtonen, & Korkeila, 2010). Prenatal smoke exposure has been associated with diverse externalizing problems including attention deficit hyperactivity disorder, conduct disorder, antisocial behavior, and substance abuse (Brennan, Grekin, Mortensen, & Mednick, 2002;Button, Maughan, & McGuffin, 2007;Ernst, Moolchan, & Robinson, 2001;Linnet et al, 2003;Nomura, Marks, & Halperin, 2010;Rogers, 2009). …”
mentioning
confidence: 99%
“…Maternal smoking is a risk factor for many psychiatric disorders (Blood-Siegfried and Rende, 2010;Button et al, 2007;Ernst et al, 2001;Fried and Watkinson, 2001;Jacobsen et al, 2007;Milberger et al, 1996Milberger et al, , 1998Pauly and Slotkin, 2008;Schmitz et al, 2006;Thapar et al, 2003;Tong and McMichael, 1992) and is still a common practice according to Substance Abuse & Mental Health Services which reported in 2012 that one in five women smoke during pregnancy. In addition to being an important issue in its own right, prenatal nicotine exposure has gained considerable traction as a suitable model for impulsive behavior as seen in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a lot of original papers and several review articles [2,[51][52][53][54][55] have been published on the associations of prenatal maternal active or passive smoking and/or postnatal child environmental tobacco smoke exposure with ADHD or ADHD-related disorders in children of different ages. concluded that magnitude of the association between smoking during pregnancy and ADHD symptoms was significantly higher in related pairs (β = 0.1; p < 0.02) than in unrelated pairs (β = -0.05; p > 0.1) which confirmed the inherited effect.…”
Section: Tobacco Smoke Exposure and Adhd Or Adhd Symptomsmentioning
confidence: 99%